PENGARUH STRUKTUR KEPEMILIKAN DAN PENGUNGKAPAN ESG TERHADAP NILAI PERUSAHAAN DENGAN KUALITAS AUDIT SEBAGAI VARIABEL MODERASI - Harianja, Silvana; Sai Maruli, Riky; Siagian, Harlyn (Jurnal Ekonomi Sakti, 2026)
This research examines the influence of institutional ownership, foreign ownership, and Environmental, Social, and Governance (ESG) disclosure on firm value, with audit quality positioned as a moderating variable. The study utilizes secondary data from 28 consumer non-cyclical firms listed on the Indonesia Stock Exchange over the 2022–2024 period. Data analysis is conducted using multiple linear regression and Moderated Regression Analysis (MRA) with SPSS version 27. The results indicate that institutional ownership has a negative and significant effect on firm value, while foreign ownership and ESG disclosure do not exhibit a significant influence. Audit quality, however, shows a positive and significant impact on firm value. Furthermore, audit quality does not moderate the relationship between institutional ownership and firm value, but it enhances the effect of foreign ownership and ESG disclosure on firm value.